EVALUASI STANDARD OPERATIONAL PROCEDURE PELAYANAN RESEP DI PUSKESMAS CIBUNGBULANG KABUPATEN BOGOR PERIODE MARET s/d APRIL 2018 - Esa Nylidia; Muhammad Afqary; Ariyansyah (Sekolah Tinggi Teknologi Industri dan Farmasi Bogor, 2018)
Prescription care is an integral part of pharmaceutical care at Primary Health Facility. Evaluation of prescription care standard at Primary Health Facility Cibungbulang was done by comparing the implementation of prescription care in Primary Health Facility with prescription prescribing standard according to Permenkes No 74 of 2016 about standard of pharmaceutical care at Primary Health Facility. A descriptive observational study was conducted on 324 samples. Data were collected using an observation table. The results showed that the date of prescribing, dosage, quantity of drug, rules of procedure and technique of use, accuracy of dose, time of drug use, preparation / compounding, delivery was done well with percentage of 100%. While other components such as patient id, paraf doctor, drug form, availability, drug side effects, label or etiquette, the provision of drug information that has not met the Pharmaceutical Care Standard in Primary Health Facility.